Immune escape of Staphylococcus aureus mediated by osteocyte lacuna-canalicular network leads to persistent and uncured bone infection - Rong, Zhigang; Chen, Xiaozhen; Qin, Leilei; Wang, Xiaohua; Luo, Fei; Zou, Quanming; Zeng, Hao (Frontiers in Cellular and Infection Microbiology, 2025)
Bone infections, specifically chronic osteomyelitis, are characterized by recurrent episodes. They are considered intractable clinical diseases as they require protracted and difficult-to-cure courses. Staphylococcus aureus (S. aureus) is the most common pathogen responsible for bone infections and has high destruction rates. Previous literature has indicated that during S. aureus osteomyelitis, immune evasion mainly involves three mechanisms: biofilm formation, intracellular infection, and abscess formation. However, recently, it was observed that S. aureus can enter and persist for a long time in the Osteocyte lacuno-canalicular network (OLCN), a bone microstructure. Furthermore, it has been found to successfully evade the host’s immune system via natural physical barriers, chemical properties, and bone microstructure’s immune escape mechanisms. Therefore, S. aureus bone infections are more difficult to cure than soft-tissue infections. Currently, there are only a few studies on OLCN invasion by S. aureus, and the clinical evidence is not sufficient. Therefore, this review aimed to combine relevant published literature on the OLCN-mediated immune escape of S. aureus to elaborate on the pathological mechanisms associated with protracted and difficult-to-cure bone infections. The findings will provide a scientific basis and theoretical foundation for future comprehensive analysis of how S. aureus invades OLCN and novel treatment strategies for bone infections.